PENETAPAN KADAR MINERAL BESI DAN KALIUM PADA DAUN SINGKONG (Manihot esculenta Crantz) MENGGUNAKAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Ridwanto, Ridwanto; Dalimunthe, Gabena Indrayani; Isnaria, Vita (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Fresh vegetables are foodstuffs that contain lots of vitamins and minerals that are important for the body (Ayu, 2002). There are two types of cassava leaves, namely, ordinary cassava leaves and curly cassava leaves. Cassava leaves contain minerals and vitamins, including calcium, iron, magnesium, protein, fat, carbohydrates, phosphorus, vitamin A, vitamin B and vitamin C. This study aims to determine the mineral levels of iron, calcium and magnesium in ordinary cassava leaves. This research includes a dry destruction process and then quantitative analysis of iron, calcium, and magnesium using the atomic absorption spectrophotometry (AAS) method, namely ferrous metal at a wavelength of 248.3 nm, calcium metal at a wavelength of 422.7 nm and magnesium metal at a wavelength of 248 nm. 285.2 nm wave. The advantages of this method are selective, sensitive and simple. The results showed that the mineral content in cassava leaves were iron (4.1384 -+ 0.2.607) mg/100g, calcium (8.058 -+ 9.0230) mg/100 and magnesium (4.096 -+ 0.0351) mg/100g.